Post-Entry Expansion in Banking: The Case of Portugal - Barros, Pedro Pita (1995)
The deregulation of the Portuguese banking industry from a system with administratively fixed interest rates and entry controls to a freer market regime has been steady over the last decade. Removal of entry constraints bee given rise to strong growth in breaches as the result of a past-entry game. Behavior differences between incumbents and entrants are observed. Surprisingly, no response of incumbents to entrants is found. Incumbent banks seem to follow each other in expansion patterns. Among incumbents, privatized beaks were more, prone to breach expansion, revealing a strong effect associated with entry by acquisition.